On the correct way to supplicate the gods in Seven against Thebes. - González-González, María Marta (Universidad de Aveiro, 2023)
The Chorus in Seven against Thebes is made up of maidens who have the important task of supplicating the gods in the crucial moment before battle, and they must do so correctly for their plea to be effective. This is one of the central themes in Aeschylus’play: what is the correct way to supplicate? Here, I suggest that the Chorus maidens’ behaviour is both rational and effective, and that an examination of the statues of the gods occupying the stage and the maner in which the Chorus invokes them is highly illuminating as regards the maidens’ religiosity
Keywords: Esquilo. Los siete contra Tebas - Crítica e interpretación; Ritos y ceremonias - Grecia; Religión griega; Aeschylus; Greek religion